2017
DOI: 10.1007/s10826-017-0821-6
|View full text |Cite
|
Sign up to set email alerts
|

I’ll Never Forgive You: High Conflict Divorce, Social Network, and Co-Parenting Conflicts

Abstract: The relation between divorce, co-parenting conflicts, and children’s adjustment problems has been well established. An unresolved question for research and clinical interventions, however, is how conflicts between parents are maintained and/or escalate. This cross-sectional research tested the hypothesis that co-parenting conflicts in divorced couples are associated with perceived social network disapproval and that this relation is mediated by parents’ tendency to forgive each other. In Study 1, a convenience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 72 publications
0
31
0
8
Order By: Relevance
“…The concept of 'high-conflict divorce' refers to situations where parents remain in patterns of interaction characterized by long-lasting and bitter disputes over child-related concerns for several years after separation (Anderson et al 2010;Birnbaum & Bala, 2010). Research has consistently demonstrated that such prolonged conflicts between parents after divorce can be detrimental for children's well-being and psychosocial health (Amato, 2000;Amato & Keith, 1991;DeBoard-Lucas et al 2010;Emery, 1999;Fincham et al 1994;Grych, 2005;Lansford, 2009;Visser et al 2017).…”
Section: Separation and Divorce In The Norwegian Contextmentioning
confidence: 99%
“…The concept of 'high-conflict divorce' refers to situations where parents remain in patterns of interaction characterized by long-lasting and bitter disputes over child-related concerns for several years after separation (Anderson et al 2010;Birnbaum & Bala, 2010). Research has consistently demonstrated that such prolonged conflicts between parents after divorce can be detrimental for children's well-being and psychosocial health (Amato, 2000;Amato & Keith, 1991;DeBoard-Lucas et al 2010;Emery, 1999;Fincham et al 1994;Grych, 2005;Lansford, 2009;Visser et al 2017).…”
Section: Separation and Divorce In The Norwegian Contextmentioning
confidence: 99%
“…Közvetlenül a válást követő időszakban a szülők általában ellenségesebbek egymással, de a konfliktusos viszony a felek között egy-két éven belül javulni szokott (Bonach 2005;Visser et al 2017). Szintén fontos a volt párok viszonyában az, hogy elégedettek-e a gyermekfelügyelet rendezésével és a tartásdíj mértékével.…”
Section: A Szülők Interperszonális Kapcsolataiunclassified
“…Maintaining a romantic relationship does not only involve the romantic partners themselves but also a network of people who may provide information and support (Canary & Stafford, 1992;Cox et al, 1997;Felmlee, 2001;Visser et al, 2017). Among the various communication technologies, social network sites (SNSs), like Facebook, have both private and public affordances which may facilitate couples' access to their social network.…”
Section: Introductionmentioning
confidence: 99%